In vitro cytochrome P450‐ and transporter‐mediated drug interaction potential of 6β‐hydroxy‐21‐desacetyl deflazacort—A major human metabolite of deflazacort. Issue 2 (21st March 2021) - Ma, Jiyuan; Beers, Brian; Manohar, Ravi; Roe, Stephen; Colacino, Joseph M.; Kong, Ronald
Abstract: 6β‐Hydroxy‐21‐desacetyl deflazacort (6β‐OH‐21‐desDFZ) is a major circulating but not biologically active metabolite of deflazacort (DFZ). In vitro studies were performed to evaluate cytochrome P450 (CYP)‐ and transporter‐mediated drug interaction potentials of 6β‐OH‐21‐desDFZ. Up to 50 µM, the highest soluble concentration in the test system, 6β‐OH‐21‐desDFZ weakly inhibited (IC50  > 50 µM) the enzyme activity of CYPs 1A2, 2B6, 2C8, 2C9, and 2D6, while moderately inhibiting CYP2C19 and CYP3A4 with IC50 values of approximately 50 and 35 μM, respectively. The inhibition was neither time‐dependent nor metabolism‐based. Incubation of up to 50 µM 6β‐OH‐21‐desDFZ with plated cryopreserved human hepatocytes for 48 h resulted in no meaningful concentration‐dependent induction of either mRNA levels or enzyme activity of CYP1A2, CYP2B6, or CYP3A4. In transporter inhibition assays, 6β‐OH‐21‐desDFZ, up to 50 µM, did not show interaction with human OAT1, OAT3, and OCT2 transporters. It weakly inhibited (IC50  > 50 µM) human MATE1, MATE2‐K, and OCT1 transporter activity, and moderately inhibited human MDR1, OATP1B1, and OATP1B3 transporter activity with IC50 values of 19.81 μM, 37.62 μM, and 42.22 μM, respectively. 14 C‐6β‐OH‐21‐desDFZ was biosynthesized using bacterial biotransformation and the subsequent study showed that 6β‐OH‐21‐desDFZ was not a substrate for human BCRP, MDR1, MATE1, MATE2‐K, OAT1, OATP1B1, OATP1B3, and OCT2 transporters, but appeared to be an in vitro substrate for the human OAT3 uptake transporter. At plasma concentrations of 6β‐OH‐21‐desDFZ seen in the clinic, CYP‐ and transporter‐mediated drug–drug interactions are not expected following administration of a therapeutic dose of DFZ in Duchenne muscular dystrophy (DMD) patients.